Distributional effects of water tariff reforms: An empirical study for Lima, Peru - Julia Alexa Barde; Paul Lehmann (Helmholtz-Zentrum für Umweltforschung (UFZ), 2013)
This study analyzes the affordability and distributional implications of water tariff reforms for poor water customers under means-tested tariffs in comparison to increasing block tariffs (IBTs) using volumetric targeting. For this purpose, we employ a unique data set for Lima, Peru. Our analysis reveals that from a pro-poor perspective, the performance of means-tested tariffs is mixed. On the one hand, they distribute more income to poor households than the IBTs, given the assumption that the overall revenue to the water supplier remains constant. On the other hand, the share of poor customers who actually benefit from water subsidies declines with means-testing. Nevertheless, means-tested tariffs clearly outperform IBTs in terms of excluding non-poor customers from being subsidized. These findings should be generalized with care as the performance of the tariff crucially depends on the cut-off value for cross-subsidies and the block prices chosen under volumetric targeting and on the design of the means-test. Our analysis further suggests that a proper assessment of individual welfare effects should take household size into account and rest on a broad set of affordability and distributional indicators. Interestingly, our results are relatively insensitive to the price elasticity of water demand.
Keywords: 330